PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA SUBTEMA BENDA TUNGGAL DAN CAMPURAN - Dwi Nola Sumiati dwi; Yuyun Elizabeth; Nita Karmila (STKIP Subang, 2023)
Dwi Nola Sumiati, 037118162. The Effect of Application of Problem Based Learning Model on Student Learning Outcomes of Single and Mixed Objects in Class V Elementary School. Thesis of Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Pakuan University, 2022. This research is a quasi-experimental research. This study aims to determine the effect of applying the Problem Based Learning model on student learning outcomes. This research was conducted at the Bojong Kiharib State Elementary School, Cigombong District, class V A and V B in the even semester of June. The calculation of the N-Gain of the Problem Based Learning model is 63 and the calculation of the N-Gain of the Discovery Learning model is 27. The researcher also conducted a normality test with the Liliefors test for both samples of normal distribution because both samples were smaller than Ltabel. In the Problem Based Learning class group, the value of Lhitung ≤ Ltabel is 0,430 ≤ 0,173, in the Discovery Learning class group Lhitung ≤ Ltabel is 0,336 ≤ 0,173. Then in the homogeneity test the data is homogeneous because it is smaller than Ftabel, the value is 1,42 ≤ 2,01. Furthermore, in the hypothesis test, thitung of 53,3 is greater than ttabel of 2,01063, indicating that H0 (zero hypothesis) is rejected and Ha (alternative hypothesis) is accepted. Based on the results of the research above, it can be stated that the application of the Problem Based Learning model has an influence on learning outcomes.